Analysis of the Plastid Genome Sequence During Maize Seedling Development - Tripathi, Diwaker; Oldenburg, Delene J.; Bendich, Arnold J. (Frontiers in Genetics, 2022)
Shoot development in maize progresses from small, non-pigmented meristematic cells to expanded cells in the green leaf. During this transition, large plastid DNA (ptDNA) molecules in proplastids become fragmented in the photosynthetically-active chloroplasts. The genome sequences were determined for ptDNA obtained from Zea mays B73 plastids isolated from four tissues: base of the stalk (the meristem region); fully-developed first green leaf; first three leaves from light-grown seedlings; and first three leaves from dark-grown (etiolated) seedlings. These genome sequences were then compared to the Z. mays B73 plastid reference genome sequence that was previously obtained from green leaves. The assembled plastid genome was identical among these four tissues to the reference genome. Furthermore, there was no difference among these tissues in the sequence at and around the previously documented 27 RNA editing sites. There were, however, more sequence variants (insertions/deletions and single-nucleotide polymorphisms) for leaves grown in the dark than in the light. These variants were tightly clustered into two areas within the inverted repeat regions of the plastid genome. We propose a model for how these variant clusters could be generated by replication-transcription conflict.